MATHEMATICS EDUCATION STUDENT PERCEPTIONS OF ONLINE LEARNING FOR IT-BASED DATA ANALYSIS COURSES THAT ARE INTEGRATED WITH CHARACTER VALUES - Suripah Suripah; Firdaus Firdaus; Fini Rezy Enabela Novilanti (FKIP Universitas Muhammadiyah Tangerang, 2022)
The learning held is expected to be an inspiration for students and to integrate character values. However, due to the Covid-19 pandemic, students have various perceptions of the implementation of lectures and related aspects. Therefore, the purpose of this study was to describe students' perceptions of the implementation of online learning at the Islamic University of Riau. This study uses a quantitative descriptive approach. Students' perceptions of the implementation of learning are carried out by giving a questionnaire that refers to three components, namely: lecturer competence, learning process components, and infrastructure components. Data was collected using an online questionnaire using Google Form which was distributed to 117 students of the IT-Based Statistical Data Analysis course by purposive random sampling. The results showed that the competence component of the lecturers obtained the highest level of perception, namely 85.16%, the facilities and infrastructure components as much as 84.55%, and the learning process component as much as 80.16%. This shows that the success of learning according to student perceptions is largely determined by the competence of the lecturer, while the facilities and infrastructure, as well as the learning process, support the success of all related components. In general, it can be concluded that students' perceptions of the implementation of online lectures in the IT-Based Data Analysis course at the Islamic University of Riau gave a positive response with a perception rate of 83.29%.